A member of the TERMINAL FLOWER 1/CENTRORADIALIS gene family controls sprout growth in potato tubers. (3rd November 2018) - Morris, Wayne L; Alamar, M Carmen; Lopez-Cobollo, Rosa M; Castillo Cañete, Javier; Bennett, Mark; Van der Kaay, Jeroen; Stevens, Jennifer; Kumar Sharma, Sanjeev; McLean, Karen; Thompson, Andrew J; Terry, Leon A; Turnbull, Colin G N; et al.
Abstract : Transgenic experiments demonstrate that TERMINAL FLOWER 1/CENTRORADIALIS is associated with potato tuber sprout growth during storage, and with the regulation of cytokinin and ABA levels. Abstract: Potato tuber bud dormancy break followed by premature sprouting is a major commercial problem which results in quality losses and decreased tuber marketability. An approach to controlling premature tuber sprouting is to develop potato cultivars with a longer dormancy period and/or reduced rate of sprout growth. Our recent studies using a potato diploid population have identified several quantitative trait loci (QTLs) that are associated with tuber sprout growth. In the current study, we aim to characterize a candidate gene associated with one of the largest effect QTLs for rapid tuber sprout growth on potato chromosome 3. Underlying this QTL is a gene encoding a TERMINAL FLOWER 1/CENTRORADIALIS homologue (PGSC0003DMG400014322). Here, we use a transgenic approach to manipulate the expression level of the CEN family member in a potato tetraploid genotype (cv. Désirée). We demonstrate a clear effect of manipulation of StCEN expression, with decreased expression levels associated with an increased rate of sprout growth, and overexpressing lines showing a lower rate of sprout growth than controls. Associated with different levels of StCEN expression were different levels of abscisic acid and cytokinins, implying a role in controlling the levels of plant growth regulators in the apical meristem.